Myths and utopias in the novels Nuestro pan and Don Goyo - Robalino, Vicente (2017)
This research sets out the process of nature´s mythological-symbolical transfiguration made by the cholo and the montubio of the Ecuadorian coast, depicted by two novels of the 1930´s generation, Nuestro pan, by Enrique Gil Gilbert and Don Goyo by Demetrio Aguilera Malta. This process implies, at the same time, the assumption of a utopia, that is, a collective hope, related to the possibility that this transfigured nature may be maintained, in spite of of the irruption of modern life (internal migrations, external migrations, implementation of the machine in the cultivation of rice) that threatens to destroy all this collective hope, in which orality plays a very important role.